Association of age at onset of migraine with family history of migraine in children attending a pediatric headache clinic: A retrospective cohort study. (July 2015) - Eidlitz-Markus, Tal; Haimi-Cohen, Yishay; Zeharia, Avraham
Aim: Migraine is known to run in families and has long been considered a strongly heritable disorder. This study sought to evaluate the relationship between age at onset of pediatric migraine and family history of migraine. Methods: Review of the medical files of the headache clinic of a tertiary pediatric medical center yielded 344 children with migraine for whom details on migraine in family members were available. Results: Mean age of the cohort was 11.69 ± 3.49 years, and mean frequency of headache per month, 13.68 ± 11.26. Mean age at migraine onset in patients with a negative parental history was10.48 ± 3.39 years; in patients with one parent with migraine, 8.84 ± 3.72 years; and in patients with both parents with migraine, 7.32 ± 3.22 years ( p  < 0.001).The duration of migraine attacks (in hours) was significantly longer in patients with any family member with migraine than in those with no family history ( p  = 0.026). Conclusions: Among children attending a tertiary pediatric headache clinic, migraine appears at a younger age in those with parental history of migraine than in those with a negative family history. The findings suggest that having a genetic background of migraine makes a child more susceptible to migraine earlier in life than a child without a family history.